INDONESIA STRATEGY IN INCREASING ECONOMIC COOPERATION IN AFRICAN COUNTRIES - Muhammad Afif Fadhli Az Zamzami,; Nur Azizah, (Jurnal Sosial Humaniora, 2024)
Indonesia’s economic cooperation in Africa is the government’s goal in improving the region’s trade balance. This research examines the strategies implemented by the government to increase economic cooperation in the African region. The government has a vital role in implementing economic cooperation for the economic development of a country. This research uses a qualitative approach. The primary and secondary data were obtained directly from face-to-face interviews with resource persons at the Asia Pacific and Africa Region Policy Centre, Ministry of Foreign Affairs. Secondary data was obtained through literature studies, literature in scientific journals, books, and official websites. Researchers analysed the data in three ways: (1) Data reduction, (2) Data presentation, and (3) Conclusion. This research approach uses the theory of liberal international trade and the concept of economic diplomacy. The result of this study is the strategies used by the government to increase economic cooperation in Africa, namely Comprehensive Market Research, Economic Partnership, and Preferential Trade Agreement. The government’s strategy positively impacts Indonesia’s trade surplus in Africa. It is noted that the value of Indonesian exports in Africa has increased by around 10.36%. Theoretical implication: The results of this study confirm previous research, especially in terms of improving Indonesia’s economic cooperation strategy in the African region. Practical implications can guide the government in making decisions related to economic diplomacy relations in Africa. Recommendations: The Government need to increase its role in encouraging parties to export to the African region.